2016
DOI: 10.1515/ljss-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

The Application and Effectiveness of Yoga in Prevention and Rehabilitation of Sport Injuries in Athletes Participating in Competitive Sport

Abstract: The purpose of the study is to review literature for scientific studies about application and effectiveness of yoga in rehabilitation & prevention of sports injuries in athletes participating in competitive sports. The author conducted a comprehensive search of open access articles of major scientific databases including PuBMed, SCIENCEDIRECT, EBSCO, SCOPUS, Web of Science, etc.. No significant scientific studies were found relating to the application of yoga in rehabilitation and prevention of sport injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Owing to a lack of high-quality evidence, Breedvelt et al’s meta-analysis suggested that the effectiveness of meditation, yoga, and mindfulness on depression, anxiety, and stress in college students should be interpreted with caution [ 33 ]. In Ravi’s [ 34 ] recent review on the application of yoga intervention in the rehabilitation and prevention of injury in competitive sports, which included only four studies, he suggested that it was possible to prevent non-contact injuries by including yoga programs in exercise training and that more research was needed. Consequently, this study evaluated the effects of yoga on movement patterns and mindfulness among collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to a lack of high-quality evidence, Breedvelt et al’s meta-analysis suggested that the effectiveness of meditation, yoga, and mindfulness on depression, anxiety, and stress in college students should be interpreted with caution [ 33 ]. In Ravi’s [ 34 ] recent review on the application of yoga intervention in the rehabilitation and prevention of injury in competitive sports, which included only four studies, he suggested that it was possible to prevent non-contact injuries by including yoga programs in exercise training and that more research was needed. Consequently, this study evaluated the effects of yoga on movement patterns and mindfulness among collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of yoga produces a physiological state opposite to that of the flight-or-fight stress response and with that interruption in the stress response, a sense of balance and union between the mind and body can be achieved [3]. Yoga is practiced in sports for injury prevention [4] as well as to enhance the performance [5,6] through achieving the peak level of physical fitness. It has been documented through several researches that yoga intervention improves the athletic performance in different sports by enhancing their flexibility, muscle strength and endurance and cardiovascular performance [5,[7][8][9], physiological health factors such as heart rate, diastolic blood pressure, immune function and muscle soreness [7,8,[10][11][12] and mental fitness [13][14][15].Yoga increases flexibility and the effects are seen as early as six weeks, even if the participants are only training once a week [16][17][18].…”
Section: Introductionmentioning
confidence: 99%